Analisis Isi Pesan Dakwah Dalam Film Insya Allah Sah Karya Benni Setiawan - Amali, Rijal Nur; Walisyah, Tengku (Fakultas Agama Islam Universitas Billfath, 2024)
This research aims to ascertain the significance of the Islamic ethical message conveyed in the film